2023
DOI: 10.7150/ijbs.81000
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the interplay between m6A modification and programmed cell death in cancer

Abstract: N6-methyladenosine (m6A) methylation, the most prevalent and abundant RNA modification in eukaryotes, has recently become a hot research topic. Several studies have indicated that m6A modification is dysregulated during the progression of multiple diseases, especially in cancer development. Programmed cell death (PCD) is an active and orderly method of cell death in the development of organisms, including apoptosis, autophagy, pyroptosis, ferroptosis, and necroptosis. As the study of PCD has become increasingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 184 publications
0
2
0
Order By: Relevance
“…At the same time, the depletion of ABCA1 could elevate SQSTM1 expression, which indicated the repression of autophagy. Recent studies have shown that m 6 A modification mediates regulation of autophagy-related genes, affecting autophagy regulatory network and programmed cell death in multiple diseases 37 , 38 . Based on the results of our study and previous reports, we may reasonably speculate that the epigenetic modification of ABCA1 mediated by m 6 A demethylase ALKBH5 may affect tumor progression of SKCM via modulating cellular cholesterol homeostasis and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the depletion of ABCA1 could elevate SQSTM1 expression, which indicated the repression of autophagy. Recent studies have shown that m 6 A modification mediates regulation of autophagy-related genes, affecting autophagy regulatory network and programmed cell death in multiple diseases 37 , 38 . Based on the results of our study and previous reports, we may reasonably speculate that the epigenetic modification of ABCA1 mediated by m 6 A demethylase ALKBH5 may affect tumor progression of SKCM via modulating cellular cholesterol homeostasis and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Given the significant role of m 6 A modification in tumor progression, there has been an increased focus on targeting m 6 A methylation and its associated proteins, such as FB23-2, a small molecule-targeting FTO in acute myeloid leukemia [46]. Numerous studies have underscored the crucial roles m 6 A methylation plays in drug resistance [47,48], radiotherapy tolerance [49,50], and programmed cell death [33,51].…”
Section: Discussionmentioning
confidence: 99%